Abscisic acid mimic-fluorine derivative 4 alleviates water deficit stress by regulating ABA-responsive genes, proline accumulation, CO2 assimilation, water use efficiency and better nutrient uptake in tomato plants - Jiménez-Arias, David; Morales-Sierra, Sarai; Suárez, Emma; Lozano-Juste, Jorge; Coego, Alberto; Estevez, Juan C.; Borges, Andrés A.; Rodriguez, Pedro L. (Frontiers in Plant Science, 2023)
Water deficit represents a serious limitation for agriculture and both genetic and chemical approaches are being used to cope with this stress and maintain plant yield. Next-generation agrochemicals that control stomatal aperture are promising for controlling water use efficiency. For example, chemical control of abscisic acid (ABA) signaling through ABA-receptor agonists is a powerful method to activate plant adaptation to water deficit. Such agonists are molecules able to bind and activate ABA receptors and, although their development has experienced significant advances in the last decade, few translational studies have been performed in crops. Here, we describe protection by the ABA mimic-fluorine derivative 4 (AMF4) agonist of the vegetative growth in tomato plants subjected to water restriction. Photosynthesis in mock-treated plants is markedly impaired under water deficit conditions, whereas AMF4 treatment notably improves CO2 assimilation, the relative plant water content and growth. As expected for an antitranspirant molecule, AMF4 treatment diminishes stomatal conductance and transpiration in the first phase of the experiment; however, when photosynthesis declines in mock-treated plants as stress persists, higher photosynthetic and transpiration parameters are recorded in agonist-treated plants. Additionally, AMF4 increases proline levels over those achieved in mock-treated plants in response to water deficit. Thus, water deficit and AMF4 cooperate to upregulate P5CS1 through both ABA-independent and ABA-dependent pathways, and therefore, higher proline levels are produced Finally, analysis of macronutrients reveals higher levels of Ca, K and Mg in AMF4- compared to mock-treated plants subjected to water deficit. Overall, these physiological analyses reveal a protective effect of AMF4 over photosynthesis under water deficit and enhanced water use efficiency after agonist treatment. In summary, AMF4 treatment is a promising approach for farmers to protect the vegetative growth of tomatoes under water deficit stress.